Determinants of Market Price per Share in Nepalese Commercial Banks: Evidence from Dividend and Earnings Indicators - Bhandari, Mohan; Pradhan, Radhe Shyam; Ghimire, Rabindra (International Research Journal of MMC, 2026)
The study seeks to identify the primary determinants of stock price fluctuations, assess their relative impact, and provide insights for investors, policymakers, and bank management. The study followed a positivist research philosophy and employed a descriptive and casual comparative research design. The population comprise of all 20 Nepalese commercial banks, among them only NEPSE listed 19 commercial banks are selected as the sample of the study using census sampling. Secondary data from annual reports and stock market records were analyzed. The study employed descriptive, correlation, and regression analysis to examine the relationships between financial variables and stock prices. Results indicate significant stock price volatility driven by both bank fundamentals and speculative activity. Earnings per share (EPS) emerged as the most influential factor, showing a strong positive correlation with market price per share (MPS). Dividends per share (DPS) and dividend payout ratio (DPR) positively affected stock prices, while dividend yield ratio (DYR) had a negative impact. The price-to-earnings (P/E) ratio demonstrated limited explanatory power. Regression analysis confirmed that EPS, DPS, and DPR collectively explained a significant portion of stock price variation, whereas DYR and P/E ratio had minor influence. Stock price movements in Nepalese commercial banks are primarily determined by profitability and dividend policies rather than speculative multiples. Investors relied more on actual financial returns, and market valuations were closely tied to earnings and dividend performance. The findings shows that the need for stronger market regulations and transparent dividend frameworks. Investors should prioritize earnings and dividends in decision-making, while bank management should maintain consistent dividend policies to enhance shareholder confidence. Academically, the study contributes to understanding stock price determinants in developing economies and encourages further research on sector-specific and macroeconomic factors.